Characterization of Ant Communities (Hymenoptera: Formicidae) in Twigs in the Leaf Litter of the Atlantic Rainforest and Eucalyptus Trees in the Southeast Region of Brazil - Debora R. de Souza; Tae T. Fernandes; José R. de Oliveira Nascimento; Silvia S. Suguituru; M. Santina de C. Morini (Psyche: A Journal of Entomology)
Fragments of Atlantic Rainforest and extensive eucalyptus plantations are part of the landscape in the southeast region of Brazil. Many studies have been conducted on litter ant diversity in these forests, but there are few reports on the nesting sites. In the present study, we characterized the ant communities that nest in twigs in the leaf litter of dense ombrophilous forests and eucalyptus trees. The colony demographics associated with the physical structure of the nest were recorded. In the eucalyptus forests, the study examined both managed and unmanaged plantations. During five months, all undecomposed twigs between 10 and 30 cm in length containing ants found within a 16-m2 area on the surface of the leaf litter were collected. A total of 307 nests and 44 species were recorded. Pheidole, Solenopsis, and Camponotus were the most represented genera. Pheidole sp.13, Pheidole sp.43 and Linepithema neotropicum were the most populous species. The dense ombrophilous forest and a eucalyptus plantation unmanaged contained the highest number of colonized twigs; these communities were the most similar and the most species rich. Our results indicate that the twigs are important resources as they help to maintain the litter diversity of dense rain forest and abandoned eucalypt crops.